The intellectual environment and its creative influence on Al-Qazwini’s thought (598-682 AH / 1201-1283 AD) - Resea. Marwa Sadiq Najman; Dr.. Ali Aqa Nouri; Dr. Thamir Noaman Mostaf (Journal of College of Education, 2025)
This study deals with the impact of the jurist and astronomer geographer Abu Yahya Zakariya bin Muhammad Al-Qazwini and his scientific role. Al-Qazwini (605-682 AH = 1208-1283 AD) was one of the prominent personalities that appeared during the seventh century AH = the thirteenth century AD, and he is one of the most prominent Arab scholars and historians in that era. The era where he contributed to the enrichment of the Arab scientific heritage. He was distinguished by many talents and a special ability in writing, using a distinguished method and approach, as he combined history, geography, astronomy, medicine, literature, plants, animals, and other sciences, as he was accurate in describing events and keen to communicate them in their parts, taking into account the scientific integrity of what He managed to do so. His books included many scientific facts that were proven in his two famous books (The Wonders of Creatures and Strange Existences), and the book (Athar al-Bilad wa Akhbar al-‘Ibad) such as human sciences, including geography, history, psychology, astronomy, natural sciences, and pure sciences, including The science of medicine, chemistry, plants, and animals, as it had a prominent role and influence in the science of art (painting and painting
Keywords: intellectual, creative, thought, Al-Qazwini